Integrating Permanent Supportive Housing and Co-Occurring Disorders Treatment for Individuals Who Are Homeless. Issue 2 (2nd April 2016) - Smelson, David A.; Zaykowski, Heather; Guevermont, Nathan; Siegfriedt, Julianne; Sawh, Leon; Modzelewski, David; Tsemberis, Sam; Kane, Vincent
ABSTRACT: Objectives : While permanent housing, addictions, and mental health treatment are often critical needs to achieve housing stability and community reintegration, few studies have systematically integrated them into a single comprehensive approach for people experiencing chronic homelessness. This pilot study examined the feasibility and preliminary outcomes of systematically integrating permanent supportive housing and an evidence-based co-occurring disorders intervention called Maintaining Independence and Sobriety Through Systems Integration, Outreach, and Networking (MISSION).Methods : This single-group open pilot enrolled 107 people with co-occurring disorders experiencing chronic homelessness from two Massachusetts inner-city and rural areas. Enrolled subjects were interested in receiving permanent supportive housing along with 1 year of MISSION services. Data were collected through baseline and 6- and 12-month follow-up assessments.Results : Participants ( M age = 49.52 years, SD = 10.61) were mostly male (76.6%), Caucasian (52.3%), and unemployed (86.0%), with an average of 8.34 years ( SD = 8.01) of homelessness. Self-reported lifetime problems with anxiety (75.7%) and depression (76.6%) were common, as was use of alcohol (30.8%), cannabis (31.8%), and cocaine (15.9%). Almost all participants (95.3%) were placed into permanent housing, which took on average 42.6 days from enrollment ( SD = 50.09). Among those placed, nearly 80% of the clients were able to retain housing through the end of the study. Overall retention was high, with 86.0% remaining in MISSION treatment until the end of the study. While there were no significant changes in rehospitalization, service utilization, or substance use, there were modest significant mental health symptom improvements from baseline to program completion.Conclusions : This pilot study suggests that co-occurring disorder interventions like MISSION are feasible to integrate with permanent supportive housing despite the somewhat differing philosophies, and preliminary data suggested substantial improvements in housing and modest improvements in mental health symptoms. While caution is warranted given the lack of a comparison group, these findings are consistent with other rigorous studies using MISSION among homeless individuals who did not receive permanent supportive housing.